Split air-conditioner noise source identification through sound intensity mapping - J. M., Zikri; M. S. M., Norhakim; M. S. M., Sani (IOP Publishing, 2024)
As the global warming takes place in years, the electrical appliances such as air-conditioner have been installed in most residential, industrial, or even in the education institution to provide better air quality and ultimately reduces the heat transfer in the ambient. Common use of split air-conditioner system to give maximum capacity in a space is responsible to the accumulated noise generated by the outdoor unit of the system. Therefore, an experimental study has been done to identify the noise rating and location of the highest noise level emitted by the system through different temperature and fan speed. The sound intensity mapping together with the sound power level will be applied to ensure the reliability of the data for the study purposes. Generally, the results indicated that the noise were concentrated at the compressor and fan blades whereas the level were observed to be higher with the lower temperature and higher fan speed operated. The highest noise level also reported as high as 99.08 dB(A) which located at the compressor. Hence it can be concluded that mitigation action is needed since considerable noise are generated by the application of air-conditioner particularly at the compressor and condenser fan.